Strategi Pengelolaan Likuiditas atas Pembiayaan Bermasalah pada Bank Sumut Syariah Cabang Pembantu Multatuli: Pendekatan Risiko dan Efisiensi - Tri IbnuRamadhanu; Kusmilawaty Kusmilawaty; Tuti Anggraini (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
High levels of Non-Performing Financing (NPF) pose a major challenge to maintaining liquidity stability in Islamic banks, as they hinder fund circulation, degrade asset quality, and heighten liquidity risk. This phenomenon is evident at Bank Sumut Syariah Sub-branch Multatuli, where the financing portfolio is dominated by consumer financing, thereby affecting the effectiveness of liquidity management. This study aims to analyze liquidity management strategies for non-performing financing through a risk and efficiency approach. A qualitative research method was employed, with data collected through interviews, observation, documentation, and an analysis of the 2025 financial reports. The analysis used the NOISE (Needs, Opportunities, Improvements, Strengths, and Exceptions) framework. The findings indicate that the high level of non-performing financing is driven by the dominance of consumer financing, suboptimal analysis of customer character, and changes in debtors' economic conditions. The strategies implemented include liquidity-priority-based collection, cash-flow-recovery-oriented restructuring, economic-value-based collateral auctions, write-off policies to improve portfolio efficiency, and optimization of the fund circulation cycle. These strategies accelerate cash flow recovery, strengthen the intermediation function, improve fund management efficiency, and maintain the bank's liquidity stability. Consequently, the bank needs to expand productive profit-sharing-based financing, strengthen financial literacy, enhance financing oversight, optimize risk management, and provide business financing assistance so that liquidity management becomes more adaptive, sustainable, and aligned with Sharia principles.